Performance of pit latrines in urban poor areas: A case of Kampala, Uganda. (October 2015) - Nakagiri, Anne; Kulabako, Robinah N.; Nyenje, Philip M.; Tumuhairwe, John B.; Niwagaba, Charles B.; Kansiime, Frank
Abstract: In many urban poor areas of Sub-Saharan Africa (SSA), demand for human excreta disposal is met, predominantly by pit latrines. This study aimed at determining the status of pit latrines (design, construction, operation and maintenance) and its influence on latrine performance (filling, smell and insect nuisance). The study was conducted on 130 pit latrines in typical urban poor areas of Kampala, Uganda. Data on design, construction, usage, operation and performance of the pit latrines was collected by interviews, observations and measurements; and analysed by descriptive statistics, bi-variate analysis and logistic regression. Results showed that the level of pit content was predicted by rain or storm water entry, terrain, cleaning before or after use and number of households using the latrine. Smell was predicted by cleanliness, stance length, superstructure material and whether the latrine was private or public. The predictor of presence of flies was the superstructure material. To improve the performance of pit latrines in urban poor areas, researchers and practitioners should develop local latrine design standards (dimensions, construction materials and number of users) and cleaning guidelines for local policy makers to implement. Highlights: Study determined influence of pit latrine designs and operation on their performance. Level of pit content was predicted by rain/storm water entry, cleaning and numbers of users. Smell depends on latrine cleanliness, stance size, superstructure material and if it is private or public. Superstructure material has an influence on fly presence in the pit latrine. Latrine standards for slums should be developed and implemented.